A HISTORY OF EDUCATION: THOUGHT AND PRACTICE (Author: Margaret Gillett) - Mowat, Alex S. (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1966)
Margaret Gillett. A History of Education: Thought and Practice. Toronto: McGraw-Hill of Canada, 1966, 443 pp.